2014
DOI: 10.1111/asj.12226
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of climatic conditions to fecal corticosterone levels of captive cheetahs reared in Japan

Abstract: To assess the stress level of cheetahs reared in Japan and to identify the prime components of the climatic conditions that affect their thermal stress, fecal corticosterone was monitored for 8 months from May to the following January. A total of 203 fecal samples were gathered in the morning from seven adult cheetahs that were kept at a zoological garden in Wakayama, Japan. Cheetahs were on exhibit singly or together with a harmonious conspecific during the day, but housed singly at night. Although the monthl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The prey of our cheetahs, as identified after some hunts (Table S1), was not unexpected given that cheetahs preferentially select medium-sized (<60 kg) prey (Schaller 1968;Mills et al 2004;Hayward et al 2006) with non-random selection for juveniles of medium to large prey (Schaller 1968;Pienaar 1969;Mills et al 2004). Potentially, the unusually high rainfall that occurred at the study site may have been stressful for our cheetahs (Uetake et al 2014) as it would have changed the vegetation structure and density throughout the course of the study, a factor for which we were unable to account in our analyses. However, cheetahs hunt successfully in dense vegetation with little difference in hunt distance or speed reached within different habitats (Wilson et al 2013).…”
Section: Figurementioning
confidence: 85%
See 1 more Smart Citation
“…The prey of our cheetahs, as identified after some hunts (Table S1), was not unexpected given that cheetahs preferentially select medium-sized (<60 kg) prey (Schaller 1968;Mills et al 2004;Hayward et al 2006) with non-random selection for juveniles of medium to large prey (Schaller 1968;Pienaar 1969;Mills et al 2004). Potentially, the unusually high rainfall that occurred at the study site may have been stressful for our cheetahs (Uetake et al 2014) as it would have changed the vegetation structure and density throughout the course of the study, a factor for which we were unable to account in our analyses. However, cheetahs hunt successfully in dense vegetation with little difference in hunt distance or speed reached within different habitats (Wilson et al 2013).…”
Section: Figurementioning
confidence: 85%
“…Not only were cheetahs able to prevent excessive rises in body temperature, but they were also able to sustain relatively high minimum 24-h body temperatures, despite ambient temperatures below freezing on occasion. Captive cheetahs may be thermally stressed on cold days as they display elevated corticosterone production at low air temperatures (Uetake et al 2014). In a high-altitude habitat, free-living cheetahs preferred locations with more solar radiation (Welch et al 2015), although such behavior will not help them maintain homeothermy at night.…”
Section: Figurementioning
confidence: 99%
“…This indicates that there may have been some different factors (aside from visitor presence or absence) that were underlying the observed significant increases in fGM concentrations. A study by Uetake et al [ 45 ] revealed a trending decrease in cheetah fGM concentrations within the summer months and high fGM concentrations on the day after a strong decrease in air temperature—hypothesizing sensitivity to cold temperatures. This is contradictory to that revealed in our study—indicating that it may not be simply seasonal fluctuations causing the increased fGM concentrations in cheetahs at the end of the summer.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously determined that glucocorticoid metabolites can be reliably extracted from fecal samples in both target species (giraffe [ 44 ], cheetah [ 45 ]). A double-antibody corticosterone enzyme immunoassay (EIA) (CJM006, 1:100,000, C. Munro, University of California, Davis, CA, USA) was used for both species.…”
Section: Methodsmentioning
confidence: 99%
“…In Japan, fecal corticosterone was monitored on seven cheetahs between two seasons (spring to winter) to identify if there was a relationship between the climatic conditions and corticosterone levels in cheetahs. The study showed that cheetahs were susceptible to climatic variations as suggested by higher fecal corticosterone concentrations, caused by the decrease in temperature [30]. This temperature change could be a possible stressor for the cheetahs.…”
Section: Extrinsic Factors 411 Captive Living Conditionsmentioning
confidence: 89%